The Gamification of Online Course to Increase Digital Marketing Skills of MSMEs in Sukabumi - Aldila Rizkiana; Zahra Khalisabira (REKA ELKOMIKA: Jurnal Pengabdian kepada Masyarakat, 2023)
The various platforms and social media available for selling online create the need for MSMEs to study and analyze the most effective platforms or social media to sell online. The gamified online learning platform is one of the solutions to make learning more easily accessible and sustainable. We followed Gamification Service Framework Application Model, from problematization, building, intervention, and evaluation to design the gamified online learning platform. The gamified online learning platform we developed proved to increase MSMEs' digital marketing skills effectively. The participants have 82.8% of completion level and an average overall quiz score of 75.3 out of 100. The benefit of gamified digital marketing online course we held in Sukabumi includes gaining new digital marketing knowledge, building the network, increasing production capacity, and marketing reach. Some drawbacks to using gamified digital marketing online courses include lack of interaction, material variation, continuous guidance, and obsolete information.